Editorial: Thinking with Migration, Sexuality, Gender Identity, and Transactional Sex - Shah, Svati (Anti-Trafficking Review, 2022)
This article introduces a special issue of Anti-Trafficking Review that bridges the fields of queer, migration, and critical trafficking studies by examining the implications of heightened juridical recognition of sexual orientation and gender identity for debates on migration, sex work, and human trafficking. The issue proceeds from the insight that, as the legibility of queer and trans* (i.e., lesbian, gay, bisexual, transgender, queer, intersex, and all non-binary and non-heteronormative forms of sexuality and gender identity) moves forward, it appears to de-emphasise the explicit connections that sexuality- and gender-based social movements have historically drawn between identity, governance, and material survival. In emphasising questions of survival, this issue both recuperates queer and non-cisnormative subjects within debates on transactional sex, and shows how a queer theoretical sensibility can offer new insights for established critiques in the field.